2016
DOI: 10.4314/bajopas.v8i2.30
|View full text |Cite
|
Sign up to set email alerts
|

Effect of homogenates of avocado pear (<i>Persea americana</i>) seeds and fluted pumpkin (<i>Telfairia occidentalis</i>) leaves coadministered with anti-tuberculosis drugs on liver enzymes of albino rats

Abstract: This study evaluated the effects of aqueous homogenates of avocado pear (Persea americana) seeds and fluted pumpkin (Telfairia occidentalis) leaves co-administered with anti-tuberculosis drug on liver enzymes of albino rats. Twenty (20) albino rats were divided into five (5) groups (of four rats each) designated as I, II, III, IV and V (which is the normal control). A dose of 5.14mg/kg body weight of a first line anti-tuberculosis drug (a combination of isoniazid, rifampicin, pyrazinamide and ethambutol) was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This is in consonance with some previous similar studies which had earlier showed the ameliorative effect of T. occidentalis on the liver following its inducement with varied forms of hepatotoxins. [24][25][26][27][28]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in consonance with some previous similar studies which had earlier showed the ameliorative effect of T. occidentalis on the liver following its inducement with varied forms of hepatotoxins. [24][25][26][27][28]…”
Section: Discussionmentioning
confidence: 99%
“…22 [22] to mention only a few. A number of studies have shown the hepatoprotective potentials of TO [23][24][25][26][27][28] in various countries including other parts of Nigeria but researches in this regards seems to be scanty in the South Eastern part of Nigeria and hence the study.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Avocado oil has been widely used due to its antioxidant, anti-inflammatory, anti-bacterial, anti-fungal, and immunemodulatory effects. Moreover, it has a beneficial role in lowering the blood glucose level [8,9] .…”
Section: Introductionmentioning
confidence: 99%